Role of velamentous cord insertion in monochorionic twin pregnancies: a PRISMA-compliant systematic review and meta-analysis of observational studies. (17th July 2020) - Lin, Dongxin; Fan, Dazhi; Wu, Shuzhen; Rao, Jiaming; Zhang, Huishan; Chen, Ting; Liu, Juan; Ye, Shaoxin; Zeng, Meng; Liu, Yan; Guo, Xiaoling; Liu, Zhengping
Abstract: Background: Velamentous cord insertion (VCI) has been proposed to be associated with some specific complications among monochorionic (MC) twin pregnancies. This meta-analysis and systematic review aims to determine the role of VCI in MC twin pregnancies. Methods: The PubMed, Embase and Web of Science databases and reference lists were searched for relevant studies. Outcomes of interest included twin-to-twin transfusion syndrome (TTTS), birthweight discordance (BWD) and selective intrauterine growth restriction (sIUGR). The methodological quality of the included studies was assessed by using the Newcastle-Ottawa Scale. The pooled results were calculated by means of a random or fixed effect model to obtain odds ratio with 95% confidential interval (CI). Subgroup analyses were utilized to detect the sources of heterogeneity. Results: Twenty studies were eligible for inclusion. The pooled result suggested a significant association between VCI and TTTS (OR, 1.542; 95% CI, 1.116–2.129) with a moderate level of heterogeneity ( Q test: p = .024; I 2 = 50.2%). Subgroup analysis reported single-center study, methodological quality and exclusion of laser-coagulated TTTS as the sources of heterogeneity. Another analysis revealed an increased risk of BWD among twin pregnancies with VCI (OR, 2.945; 95% CI, 2.176–3.984) with a low heterogeneity ( Q test: p = .347; I 2 = 10.5%). None of study level characteristics was found to be an influencing factor. Three studies reporting on sIUGR suggested a significant association between VCI and sIUGR. Conclusions: The meta-analysis and systematic review suggests an association between VCI and BWD and sIUGR. However, the association between VCI and TTTS may be overestimated and high-quality studies with a representative sample are needed in further research.